Family Structure and the Education Gender Gap: Evidence from Italian Provinces - Graziella Bertocchi; Monica Bozzano (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate the determinants of the education gender gap in Italy in historical perspective with a focus on the influence of family structure. We capture the latter with two indicators: residential habits (nuclear vs. complex families) and inheritance rules (partition vs. primogeniture). After controlling for economic, institutional, religious, and cultural factors, we find that family structure is a driver of the education gender gap, with a higher female to male enrollment rate ratio in upper primary schools being associated with nuclear residential habits and equal partition of inheritance. The effect tends to persist through the present day.
Keywords: E02; H75; I25; J16; N33; O15; 330; education gender gap; Italian unification; family types; inheritance; institutions; religion; convergence